Pediatric caregiver involvement in the assessment of physicians - Moreau, Katherine A; Pound, Catherine M; Eady, Kaylee (Université d'Ottawa | University of Ottawa, 2015)
Abstract Background Given the growth and benefits of consumerist and family-centred approaches to pediatric health care, there is a need to involve pediatric caregivers in the assessment of their children’s physicians. Discussion We present interconnected questions that are important to address in order to facilitate pediatric caregiver involvement in the assessment of their children’s physicians. Summary Pediatric caregivers can be valuable assessors of physicians’ non-technical skills. It is important to conduct additional research on caregiver involvement in assessment activities and create a reflective discourse on this topic. To ensure that pediatric caregivers’ assessments of physicians are formally recognized and advantageous, it is important to understand: (a) what pediatric caregivers can assess; (b) what assessment tools exist for pediatric caregivers; (c) how to create appropriate assessment tools for pediatric caregivers; (d) how to collect pediatric caregivers’ assessments; (e) how to increase the legitimacy, use, and effectiveness of pediatric caregivers’ assessments; and (f) the consequences of pediatric caregiver assessment.